Atlas Berwarna & Teks Anatomi Manusia : sistem saraf dan alat-alat sensoris Jilid 3 - KAHLE, Werner (Hipokrates, 1999)
Atlas Berwarna & Teks Anatomi Manusia : sistem saraf dan alat-alat sensoris Jilid 3